Downregulation of miR-193b in systemic sclerosis regulates the proliferative vasculopathy by urokinase-type plasminogen activator expression. Issue 1 (10th November 2014) - Iwamoto, Naoki; Vettori, Serena; Maurer, Britta; Brock, Matthias; Pachera, Elena; Jüngel, Astrid; Calcagni, Maurizio; Gay, Renate E; Whitfield, Michael L; Distler, Jörg H W; Gay, Steffen; Distler, Oliver
Abstract : Objectives: To investigate the role of microRNA-193b-3p (miR-193b) in the vascular pathophysiology of systemic sclerosis (SSc). Methods: Expression of miR-193b in skin biopsies and fibroblasts from patients with SSc and normal healthy (NH) controls were determined by real-time PCR. Transfection with miR-193b precursor and inhibitor were used to confirm targets of miR-193b. Proliferative effects of urokinase-type plasminogen activator (uPA) were determined by water-soluble tetrazolium salt-1 assay and by analysis of proliferating cell nuclear antigen expression. Fluorescence activated cell sorting analysis was performed to investigate the effect of uPA on apoptosis. For inhibition of the uPA-cellular receptor for uPA (uPAR) pathway, uPAR neutralising antibodies and low molecular weight uPA were used. Results: We found that miR-193b was downregulated in SSc fibroblasts and skin sections as compared with NH controls. The expression of miR-193b was not affected by major profibrotic cytokines and hypoxia. Induction of miR-193b in SSc fibroblasts suppressed, and accordingly, knockdown of miR-193b increased the levels of messenger RNA and protein for uPA. uPA was found to be upregulated in SSc as compared with NH controls in a transforming growth factor-β dependent manner, and uPA was strongly expressed in vascular smooth muscle cells in SSc skin section. Interestingly, uPA induced cell proliferation and inhibited apoptosis of human pulmonary artery smooth muscle cells, and these effects were independent of uPAR signalling. Conclusions: In SSc, the downregulation of miR-193b induces the expression of uPA, which increases the number of vascular smooth muscle cells in an uPAR-independent manner and thereby contributes to the proliferative vasculopathy with intimal hyperplasia characteristic for SSc.